LITERATURE STUDY: INTENSIVE CARE UNIT-TALK, A COMMUNICATION AID FOR MAINTENANCE INTUBATED INTENSIVE PATIENTS [KAJIAN LITERATUR: INTENSIVE CARE UNIT-TALK, SEBUAH ALAT BANTU KOMUNIKASI BAGI PERAWATAN PASIEN INTENSIF YANG TERINTUBASI] - Eva Chris Veronica Gultom (Nursing Current: Jurnal Keperawatan, 2019)
ICU-Talk technique is a development of Augmented Alternative Communication (AAC) method. This technique provides some features that are compiled with a database computerized. This database has a major vocabulary and vocabulary developed and is highly compatible with all patients. Systematic review to analyze the effectiveness of such devices and the like in communication in an intubated patient..Authors use some search keywords that are "Intensive Care Unit", "communication", "Patient", "intubated", "tool", Augmented Alternative Communicator using boolean "AND". literature sources to be studied is EBSCO, ScienceDirect, aacnjournals, ersjournals. There were 11 articles that have been reviewed. ICU-Talk is a practical design and consists of two interfaces. Many vocabulary is stored in this ICU-Talk database, and its usage can be through touch screen (touch screen), mouse or with one button. Each interface is colored differently and comes with animations and 250 vocabulary, as well as box-shaped and bubbles. The use of these boxes and bubbles makes it easier for users to find words / topics that suit their needs. For hospital, nurses, and nursing students to pay attention to these tools as a forms of communication with patients intubated.BAHASA INDONESIA Teknik ICU-Talk ini merupakan perkembangan dari metode Augmented Alternative Communication (AAC).Teknik ini menyediakan beberapa fitur yang disusun dengan database secara terkomputerisasi.Database ini memiliki kosakata yang utama dan kosakata yang dikembangkan dan sangat sesuai dengan semua pasien. Kajian literatur untuk menganalisa keefektifitasan alat tersebut dan sejenisnya dalam komunikasi pada pasien yang terintubasi. Penulis menggunakan beberapa kata kunci pencarian yaitu “Intensive Care Unit”, “communication”, “Pasient”, ‘intubated”, “tool”, Augmented Alternative Communicator dengan menggunakan boolean “AND”. Artikel yang digunakan berjenis full text dari database seperti EBSCO, sciencedirect, aacnjournals, ersjournals. Artikel yang didapatkan sesuai kriteria tersebut berjumlah 11 artikel. ICU-Talk ini dengan rancangan yang praktis dan terdiri dari dua pilihan tatap muka (interfaces). Banyak kosakata yang disimpan dalam database ICU-Talk ini, dan penggunaannya dapat melalui layar sentuh (touch screen), mouse atau dengan satu tombol. Masing-masing interface diberi warna yang berbeda dan dilengkapi dengan animasi serta 250 kosakata, serta berbentuk boxes dan bubbles. Penggunaan boxes dan bubbles ini mempermudah pengguna dalam menemukan kata/topik yang sesuai dengan kebutuhannya Bagi rumah sakit, perawat dan mahasiswa dapat memperhatikan alat ini sebagai bentuk komunikasi dengan pasien yang terintubasi.